Kinetics of Free Radical Polymerization of N-Substituted Amides and Their Structural Implications - Anca Aldea; Ana-Maria Albu; Alina Nicolescu; Victorita Tecuceanu (Advances in Materials Science and Engineering)
Two N-substituted amides (N-acryloyl morpholine and N-methyl-N-vinylacetamide) were polymerized in different solvents using radical initiator. The tacticity of obtained polymers was determined by 400 MHz 1H-NMR and 13C-NMR. At a given temperature, the syndiotacticity increased with increasing the solvent polarity. This solvent effect may be related to the hydrogen bonding interaction among solvent, monomer, and/or growing species. A peculiar aspect regards the steric hindrance at the nitrogen atom.